2011
DOI: 10.1007/s00521-011-0556-z
|View full text |Cite
|
Sign up to set email alerts
|

On fuzzy h-ideals in $$\Upgamma$$ -hemirings

Abstract: By means of a kind of new idea, we introduce the concepts of some kinds of fuzzy h-ideals in C-hemirings. Some new characterization theorems of these kinds of fuzzy h-ideals of a C-hemiring are also given. In particular, we show that the h-hemiregular C-hemirings can be described by using these kinds of fuzzy h-ideals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Chen et al [5] presented a new definition of soft set parametrization reduction. Research and application about soft sets can be also found in [1,2,3,6,7,9,12,14,15,21,23,24,25,33]. The most appropriate theory for dealing with uncertainties is the theory of fuzzy sets developed by Zadeh [28,29], there are many papers (see [4,16]) devoted to fuzzify the classical mathematics into fuzzy mathematics.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [5] presented a new definition of soft set parametrization reduction. Research and application about soft sets can be also found in [1,2,3,6,7,9,12,14,15,21,23,24,25,33]. The most appropriate theory for dealing with uncertainties is the theory of fuzzy sets developed by Zadeh [28,29], there are many papers (see [4,16]) devoted to fuzzify the classical mathematics into fuzzy mathematics.…”
Section: Introductionmentioning
confidence: 99%